HPV testing as an effective triage strategy in the follow-up after fertility-sparing treatment for glandular lesions of the uterine cervix - Dostalek, Lukas; Freitag, Pavel; Slovackova, Miroslava; Zima, Tomas; Komarc, Martin; Fricova, Lenka; Fucik, Tomas; Nemejcova, Kristyna; Cibula, David; Brynda, Daniel; Slama, Jiri (International journal of gynecological cancer : official journal of the International Gynecological Cancer Society, 2024)
OBJECTIVE: The management and surveillance of glandular pre-cancerous lesions of the uterine cervix present distinct challenges compared with squamous lesions, primarily attributed to the lower effectiveness of diagnostic methods such as cytology or colposcopy. This study aimed to investigate the long-term safety of fertility-sparing treatment for adenocarcinoma in situ and microinvasive adenocarcinoma of the cervix, while identifying factors associated with recurrence, with a particular emphasis on the role of human papillomavirus (HPV) testing. METHODS: We retrospectively reviewed data from all patients with histopathologically confirmed adenocarcinoma in situ or microinvasive cervical adenocarcinoma who received treatment at a single center between 2002 and 2023. The study involved the examination of consecutive surgical specimens and the follow-up details. Factors associated with recurrence were assessed in a subgroup of patients with available long-term follow-up data (at least 6 months). RESULTS: In total, 143 patients (112 with adenocarcinoma in situ and 31 with adenocarcinoma) were included in the analysis. Among the 86 patients who underwent fertility-sparing treatment, the recurrence rate was 9% (12% for adenocarcinoma in situ and 4% for adenocarcinoma) during a median follow-up period of 56.6 months (range 7-179). No patients who were HPV negative experienced recurrence during the follow-up period. In contrast, among patients who were HPV positive, the recurrence rate was 38%. Additionally, HPV 16/18 positivity displayed a notable association with a higher risk of recurrence compared with the other high-risk genotypes, although this difference did not reach statistical significance (83% vs 10%; p=0.083, log-rank). CONCLUSION: Our retrospective study demonstrated a significant association between the risk of recurrence and HPV status during the follow-up period. Consequently, long-term follow-up utilizing HPV testing and genotyping appears to be a secure alternative to a hysterectomy.
Keywords: Retrospective Studies; retrospektivní studie; Female; Humans; zachování plodnosti; lokální recidiva nádoru; Papillomaviridae; Triage; následné studie; lidé; Follow-Up Studies; Fertility Preservation; nádory děložního čípku; infekce papilomavirem; ženské pohlaví; lidé středního věku; Middle Aged; Adenocarcinoma; Papillomavirus Infections; dospělí; Adult; adenokarcinom; Neoplasm Recurrence, Local; třídění pacientů; Uterine Cervical Neoplasms